Implementasi Pembiasaan Ibadah Harian dalam Membentuk Akhlak Disiplin Siswa Di MI Guppi Pagerlor 2 Pacitan - Alifvia Nur Aini; Mokhamad Choirul Hudha (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
Islamic education emphasizes the formation of disciplined character, which can be developed through habituation from an early age. This study aims to describe the process of forming students’ disciplined character through daily worship habituation at Madrasah Ibtidaiyah Guppi Pagerlor 2. The school was selected due to its relatively small number of students and its structured and intensive worship programs. This study employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The findings indicate that the consistent and routine practice of daily worship contributes to the development of students’ discipline, particularly in terms of punctuality, compliance with rules, and responsibility. A structured guidance system, the role of teachers as educators, and the implementation of rewards and educational sanctions were identified as the main supporting factors. However, limitations in facilities and lack of family support remain challenges. Therefore, daily worship habituation plays a significant role in fostering students’ disciplined character and strengthening character education in the madrasah.